x-6x=-13-x-3x

Simple and best practice solution for x-6x=-13-x-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-6x=-13-x-3x equation:



x-6x=-13-x-3x
We move all terms to the left:
x-6x-(-13-x-3x)=0
We add all the numbers together, and all the variables
x-6x-(-4x-13)=0
We add all the numbers together, and all the variables
-5x-(-4x-13)=0
We get rid of parentheses
-5x+4x+13=0
We add all the numbers together, and all the variables
-1x+13=0
We move all terms containing x to the left, all other terms to the right
-x=-13
x=-13/-1
x=+13

You can always share this solution

See similar equations:

| 8=0.75a+12-a+4 | | 19x-1=13x-19 | | -8x+54=4x-66 | | 22x?6.2x+8=0 | | ?(x-3)-64=0 | | -9x=-3x+24 | | 6x/5-x=54 | | 6x/5-x=270 | | 0.19x+0.4(x-3)=0.01(4x-5) | | 23(9x-38)-13=23 | | (x+5)*3=x(5x-17) | | 4=0.4x=0.5x-6 | | x+5/x=5x-17/3 | | y+7=89 | | 4y+3y+2=y-4 | | z+6/4-z-15/5=3 | | 1/4(4t-8)=11/4t-t+8/8 | | 0.25x-6=0.33x | | 1/4x-6=1/3x | | X-100=-0.25x20 | | X-100=1.50x20 | | c-24=36 | | 0.2x-0.15=0.15 | | 15x=-27+6x | | 4x-63=27-x | | -0,8x-2Y=11,6 | | -15.4=7.7x | | x+7*3-x+2=53 | | 24/4(8/4$=c | | k3-5=34 | | 7^5x=11^3-x | | u+8/15=4/5 |

Equations solver categories